Scleral lens fitting and assessment strategies. Issue 1 (February 2019) - Harthan, Jennifer; Shorter, Ellen; Nau, Cherie; Nau, Amy; Schornack, Muriel M.; Zhuang, Xiaohua; Fogt, Jennifer
Highlights: There was a statistically significant difference between new and experienced scleral lens prescribers' initial use of technology in selection of a diagnostic lens. New prescribers consider base curve first and in comparison, experienced prescribers considered sagittal depth first, when making their initial scleral lens selection. All of the experienced lens prescribers reported that they estimate central corneal clearance by comparing the thickness of the central post-lens tear reservoir to scleral lens thickness using a slit lamp beam at least some of the time, and 62% of the new scleral lens prescribers reported doing so. All experienced scleral lens prescribers schedule their scleral lens follow-ups at a specific time of the day compared to only 58% of the new prescribers. After lens removal, all experienced prescribers assess conjunctival compression impression, conjunctival staining, and corneal staining. Aspects of scleral lens fitting and evaluation which have been nearly universally adopted include: 300–500 microns of central clearance is considered excessive, less than 150 μm of central clearance is insufficient, 200–300 microns of limbal clearance is deemed excessive, less than 100 μm of limbal clearance is insufficient, and none to one quadrant of conjunctival compression or blanching or billowing is considered acceptable. Abstract: Purpose: To describe prescriber reported scleral lens fitting and assessment strategies. Methods: The SCOPE (Scleral Lenses in Current Ophthalmic Practice Evaluation) study group designed and administered an IRB approved, electronic survey (REDCap) regarding current scleral lens fitting and assessment methods. The survey was distributed to attendees of the 2017 Global Specialty Lens Symposium. Results: 95 practitioners responded to the survey. Over half of the respondents, 58% (55/95) reported fitting scleral lenses for less than five years (new prescribers), and 42% (40/95) reported fitting scleral lenses for more than five years (experienced prescribers). There was a statistically significant difference between their initial use of technology (χ 2  = 21.117, p < 0.0005) in selection of a diagnostic lens. New prescribers consider base curve first (60%, 33/55), while experienced prescribers considered sagittal depth first (63%, 25/40) in their initial scleral lens selection. All of the experienced lens prescribers (100%, 39/39) reported estimating central clearance by comparing thickness of the post-lens tear reservoir to scleral lens thickness using a slit lamp beam at least some of the time, and 62% of new scleral lens prescribers (34/55; χ 2  = 19.175, p < 0.0005) reported doing so. All (100%, 40/40) experienced prescribers schedule scleral lens follow-ups at a specific time and assess conjunctival compression (100%, 40/40), conjunctival staining (100%, 39/39), and corneal staining (100%, 40/40) after lens removal. Conclusions: Practitioners with varying backgrounds and experience have added sclerals to their lens inventories. However, definite guidelines for fitting have not been developed. The results of a survey are provided; demonstrating that among practitioners with greater than 5 years of scleral lens experience, a consensus has emerged for best practices. Strategies for lens evaluation, which may inform future efforts at generating scleral fitting standards are described.